Growth of MPS-capped ZnS quantum dots in self-assembled thin films: Influence of heat treatment - Koc, Kenan; Tepehan, Fatma Zehra; Tepehan, Galip Gultekin (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2015)
The colloidal ZnS quantum dots (QDs) were prepared using 3-mercaptopropyl trimethoxysilane (MPS) molecules. Sol gel spin coating method was used to deposit the colloidal nanoparticles on a glass substrate. Several features of the MPS were made use to produce self assembled thin films of ZnS quantum dots in a SiO2 network. Produced films were heat treated in between 225 degrees C and 325 degrees C to investigate their growth kinetics. The result showed that their size changed approximately from 3 nm to 4 nm and the first excitation peak position changed from 4.6 eV to 4.1 eV in this temperature interval. The activation energy of the nanoparticles for the Ostwald ripening process was found to be 59 kJ/mol. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Growth kinetics; ZnS quantum dots; 3-mercaptopropyltrimethoxysilane; Thin films; Heat treatment; OPTICAL-PROPERTIES; AQUEOUS-SOLUTION; KINETICS; NANOCRYSTALS; SIZE; NANOPARTICLES; SILICA; CDSE; PRECURSOR; GLASS; Physics